Investigation of neuronal autoantibodies in two different focal epilepsy syndromes. - Ekizoglu, E; Tuzun, E; Woodhall, M; Lang, B; Jacobson, L; Icoz, S; Bebek, N; Gurses, C; Gokyigit, A; Waters, P; Vincent, A; Baykan, B (2014)
OBJECTIVE: Neuronal antibodies have been identified in patients with seizures as the main or sole symptom. Our aim was to investigate the prevalence of these autoantibodies in patients with focal epilepsy of unknown cause (FEoUC) and in the group having mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). METHODS: We studied anti-neuronal antibodies of consecutive adult patients diagnosed with FEoUC and MTLE-HS in our epilepsy center. The clinical and laboratory features of antibody-positive patients were compared with those of seronegative patients. The responses to therapy have also been investigated. RESULTS: Sera from 81 patients with epilepsy were tested. We found antibodies against glycine receptor (GLY-R) in 5 (6.2%), contactin-associated protein 2 (CASPR-2) in 4 (4.9%), N-methyl-d-aspartate receptor (NMDA-R) in 2 (2.5%), and voltage-gated potassium channel (VGKC)-complex in 2 (2.5%) of our patients with epilepsy. Psychotic attacks and nonspecific magnetic resonance imaging (MRI) white matter changes (WMCs) showed significant associations in seropositive patients (p = 0.003 and p = 0.03, respectively). Poor drug-response rates and total seizure counts were also higher in the seropositive patients but without reaching statistical significance. Three seropositive patients with previous epilepsy surgery showed typical histopathologic results for MTLE-HS, but not inflammatory changes. Moreover, some patients harboring these antibodies partly benefited from immunotherapy. SIGNIFICANCE: We detected neuronal antibodies in one sixth of patients with focal epilepsy, GLY-R antibodies being the leading one. Psychosis or nonspecific MRI WMCs were frequent in the seropositive group. Our results suggested that relevant antibodies should be screened for a treatment possibility in these groups.